THE POTENTIAL OF ACTIVATED CHARCOAL MADE FROM INDONESIAN JAMBI FOREST WOOD FOR HOME-USE BLEACHING TEETH - Rina Kurnianti; Retno Dwi Sari; Mira Sri Gumilar (OPI Napoli, 2023)
Introduction: Discoloration of the teeth can occur when stains damage the surface of tooth enamel. Developing treatment of teeth discoloration has increasingly due to discoloration teeth. Activated wood charcoal is one of the natural ingredients that can be used as an alternative to chemical home-use bleaching. Objective: The purpose of this study was to obtain the effectiveness of activated charcoal made from tembesu wood and bulian wood for home-use bleaching teeth Materials and Methods: This experiment was conducted at two locations: the Jambi Health Polytechnic Pharmacy Laboratory and the Jambi University Laboratory. It involved 60 samples, which were divided into six groups. The samples used in this research consisted of individuals with missing permanent teeth. The tooth color was assessed using the Vita Classical Shade Guide Tool. Charcoal derived from bulian wood and tembesu wood was mixed with toothpaste at concentrations of 10%, 20%, and 30%. Results: Our results showed a significant teeth whitening in both groups, namely Tembesu wood and Bulian. Particularly, we found that Tembesu wood, when used at concentrations of 10%, 20%, and 30%, is highly effective in teeth whitening. Specifically, at a 10% concentration of Tembesu wood, teeth whitening displayed a notable increase from day four to day 10. Meanwhile, at concentrations of 20% and 30%, teeth whitening exhibited significant improvement from day two to 10. In the case of Bulian Wood, teeth whitening was similarly effective for concentrations of 10% and 20%, with noticeable enhancement from day two to 10. For the 30% concentration, teeth whitening effectiveness increased substantially, starting from day one and continuing through day 10. Finally, no statistically significant difference between the two groups was found (p>0.05). Discussion: Tembesu wood and bulian wood at concentrations of 10%, 20%, and 30% are effectively used for teeth whitening, and there is no statistically significant difference between the two groups (p > 0.05).